Making Meaning through Multicultural Initiatives. Issue 144 (December 2013) - Elkins, Becki; Morris, Kenneth; Schimek, Gwendolyn
Abstract : This chapter discusses assessment and evaluation of multicultural initiatives by exploring two efforts implemented at a small, liberal arts college.